2008
DOI: 10.1007/s11430-008-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Major element, trace element, and Sr, Nd and Pb isotope studies of Cenozoic basalts from the South China Sea

Abstract: The whole rock K-Ar ages of basalts from the South China Sea basin vary from 3.8 to 7.9 Ma, which suggest that intra-plate volcanism after the cessation of spreading of the South China Sea (SCS) is comparable to that in adjacent regions around the SCS, i.e., Leiqiong Peninsula, northern margin of the SCS, Indochina block, and so on. Based on detailed petrographic studies, we selected many fresh basaltic rocks and measured their major element, trace element, and Sr-Nd-Pb isotope compositions. Geochemical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 52 publications
9
125
0
2
Order By: Relevance
“…Having erupted in a continental intra-plate tectonic setting (Yan et al, 2008), the second hypothesis can be ruled out for the Hainan basalts and, as discussed in Section 5.3 there is little evidence for crustal contamination in the Hainan basalts (Zou and Fan, 2010). Therefore, we argue that a recycled gabbro component was involved in the source region of the Hainan basalts.…”
Section: Lithology Of Mantle Sourcementioning
confidence: 74%
See 1 more Smart Citation
“…Having erupted in a continental intra-plate tectonic setting (Yan et al, 2008), the second hypothesis can be ruled out for the Hainan basalts and, as discussed in Section 5.3 there is little evidence for crustal contamination in the Hainan basalts (Zou and Fan, 2010). Therefore, we argue that a recycled gabbro component was involved in the source region of the Hainan basalts.…”
Section: Lithology Of Mantle Sourcementioning
confidence: 74%
“…Cenozoic continental intra-plate basalts are widespread in Southeast China, the South China Sea Basin and the Indo-China Peninsula (Zhou and Armstrong, 1982;Hoang et al, 1996;Chung et al, 1997;Zhou and Mukasa, 1997;Hoang and Flower, 1998;Ho et al, 2000Ho et al, , 2003Zou et al, 2000;Fedorov and Koloskov, 2005;Yan et al, 2008;Zou and Fan, 2010;Wang et al, 2012Wang et al, , 2013Fig. 1a), defining a potentially 'diffuse' igneous province in Southeast Asia (Hoang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…K-Ar dating of the samples dredged from the north slope of East Reed bank yield very young ages of 2.7-0.4 Ma [51]. Yan et al [52] reported K-Ar ages of basalts from the same area which range from 7.91-3.80 Ma.…”
Section: Previous Studies On Volcanic Rocks In the South China Sea Anmentioning
confidence: 99%
“…From the limited distribution of volcanism and available seismic profiles in the northern margin of the SCS, the South China continental margin does not share these characteristics, perhaps implying that the opening of the SCS was not caused by a mantle plume [52]. Likewise, the fact that all the OIB-type basalts were emplaced during the post-spreading stage, even if these rocks resulted from melting of the Hainan plume, suggests that the mantle plume may not be responsible for the opening of the SCS.…”
Section: Hainan Mantle Plume and Its Link With The Opening Of The Soumentioning
confidence: 99%
“…Judging from the data available up to now, magmatic activities in the SCS occurred mostly after but only rarely before spreading. All the trawled basalt samples form the SCS postdate the oceanic crust and should represent the products of post-spreading magmatism [26][27][28]. The most prominent post-spreading magmatism includes the volcanic sea-mount chains in the deep basin, many of which are ranged along the relict spreading ridges and lacking a systematic investigation.…”
Section: Dynamic Mechanism Of Seafloor Spreadingmentioning
confidence: 99%